PENEGAKAN HUKUM KEKERASAN DALAM RUMAH TANGGA DENGAN KONSEP KEADILAN, KEPASTIAN, KEMANFAATAN DALAM TUJUAN PEMIDANAAN - Indra Yudha Koswara (Jurnal Hukum Mimbar Justitia, 2022)
The purpose of fostering a married life should be noble but the journey does not always run smoothly, there are challenges that must be faced by every couple and how to solve each challenge, but until now the journey of fostering a household is oftentinged with violence. Sometimes the law enforcement process creates new problems including disturbed family welfare and even divorce. How is the theoretical basis for the law enforcement process against domestic violence with the concept of justice, benefits of certainty and how is the implementation of the law enforcement process against domestic violence. The purpose of this research is that law enforcement officers do not only pursue legal certainty in enforcing the law, but rather to justice and benefit which aims to maintain and restore better family relationships or rehabilitation of relationships within the family. This study uses a normative juridical approach, by examining and interpreting theoretical matters concerning the principles, conceptions, doctrines and normative laws relating to the concept of Justice, the benefits of legal certainty. Law enforcement officers have begun to implement a justice and expediency approach that is oriented to the concept of restorative justice. .that it is better if law enforcement officers in the process of law enforcement against domestic violence put more emphasis on the concept of justice and benefits for the sake of improving the relationship between the two partners in the householdKeywords: Domestic Violence, Justice, benefit.